Stories from the trenches: Experiences of Alberta pharmacists in obtaining additional prescribing authority - Charrois, Theresa; Rosenthal, M.; Tsuyuki, R. (Canadian Pharmacists Association, 2012)
Background: Pharmacists in Alberta can apply to the Alberta College of Pharmacists in order to obtain the designation of additional prescriber. This designation uniquely allows them to initiate therapy, in addition to other medication-related activities. Our objective was to examine specific experiences of pharmacists regarding the decision to apply and the application itself, and use this information to help inform other pharmacists who are considering additional prescribing. Methods: All pharmacists involved in a randomized, controlled trial being conducted in rural Alberta who had received their additional prescribing authorization (APA) were invited to participate. Pharmacists were contacted via e-mail and asked to respond to questions regarding their experiences in applying for APA. Responses were analyzed using content analysis and the identities of all respondents were kept anonymous. Results: Fourteen pharmacists were invited to participate. Review and examination of the responses revealed 3 main themes: motivation, hurdles and outcomes. Motivation can be understood as the reasons why they applied for their APA. Hurdles include any problems encountered of a personal, environmental or professional nature. Outcomes refer to how this designation has changed their practice. Discussion: Pharmacists had to address many factors that were unexpected during the application process; however, the eventual outcome of obtaining APA was deemed beneficial, both professionally and with regard to patient care. Conclusion: The information shared from these pharmacists will help other pharmacists, regardless of jurisdiction, overcome some of the challenges associated with obtaining advanced prescribing privileges.